DESCRIPTION OF SURFACE STRUCTURE OF EGGS AND FIRST INSTAR LARVAE OF AGAPANTHIA OSMANLIS REICHE & SULCY (COLEOPTERA: CERAMBYCIDAE): BASED ON SCANNING ELECTRON MICROSCOPY (Acta Entomologica Serbica, 2023)
Morphology of eggs and first instar larvae of Agapanthia osmanlis Reiche & Saulcy, 1858 (Coleoptera: Cerambycidae) are described for the first time, with illustrations of the structural features obtained using light and scanning electron microscopy (SEM). A. osmanlis feeds only on hosts in the Dipsacaceae family and collected on Cephalaria procera Fish & Lall. (Dipsacaceae) from Bayburt (Kop Mountain Pass, Turkey). The female lays single eggs inside the stalks of C. procera, where the larva feeds internally. The egg is cylindrical, white, dorsally wide, narrower toward the front and back, and rounded anteriorly and posteriorly. The egg is 3.10-3.80 (3.35) mm long and 0.45-0.85 (0.58) mm wide. Under the dissection microscope, the chorion appears to be smooth, but in scanning electron microscope (SEM) magnifications, the chorion is covered with chorionic spines except for the anterior micropylar region. Each egg possesses a knob-like micropylar process at one end. Newly emerged larvae of A. osmanlis are cylindrical, C-shaped after leaving their galleries, whitish-grey, and legless.